2005
DOI: 10.1007/s00705-005-0494-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a partitivirus from the plant pathogenic ascomycete Rosellinia necatrix

Abstract: The W8 isolate of the phytopathogenic fungus, Rosellinia necatrix that causes white root rot, contained three segments of double-stranded (ds) RNA, namely L1, L2 and M. Purified viral particles of about 25 nm in diameter contained an RNA segment with almost the same mobility as M-dsRNA, but the band was sensitive to S1 nuclease. Molecular analysis revealed that M-dsRNA consisted of two (RNA 1 and RNA 2) similarly sized species of 2299 and 2279 bp excluding an interrupted poly (A or U) tail of 16-51 bp. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…Some partitiviruses infect fruit-pathogenic fungi, e.g., Helicobasidium mompa virus (HmV) (6,17,51), Rosellinia necatrix partitivirus 1 (RnPV1) (17), RnPV2 (32), and tentative species RnPV3, RnPV4, and RnPV5 (52), while no chrysovirus is known to infect fruit-pathogenic fungi (12)(13)(14)(15)(16)(17)45). To our knowledge, this is the first report of a chrysovirus and a partitivirus infecting B. dothidea and the first report of a chrysovirus associated with the hypovirulence of a phytopathogenic fungus (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some partitiviruses infect fruit-pathogenic fungi, e.g., Helicobasidium mompa virus (HmV) (6,17,51), Rosellinia necatrix partitivirus 1 (RnPV1) (17), RnPV2 (32), and tentative species RnPV3, RnPV4, and RnPV5 (52), while no chrysovirus is known to infect fruit-pathogenic fungi (12)(13)(14)(15)(16)(17)45). To our knowledge, this is the first report of a chrysovirus and a partitivirus infecting B. dothidea and the first report of a chrysovirus associated with the hypovirulence of a phytopathogenic fungus (50).…”
Section: Discussionmentioning
confidence: 99%
“…Biocontrol measures may represent an important way to combat fungal diseases. Apart from R. necatrix and Helicobasidium mompa, no other fungi attacking fruit trees have been reported to be infected by mycoviruses (6,(11)(12)(13)(14)(15)(16)(17). Here we report on a strain of B. dothidea (LW-1) isolated from a pear tree from Wuhan, China.…”
mentioning
confidence: 95%
“…As in some other phytopathogenic fungi such as the chestnut blight fungus, Cryphonectria parasitica (16) and the white mold fungus, Sclerotinia scleotiorum (17), R. necatrix hosts a variety of viruses, including partitiviruses (18)(19)(20). For example, a field hypovirulent fungal strain, W8, was shown to be infected with a partitivirus Rosellinia necatrix partitivirus 1 (RnPV1) (21) and a novel megabirnavirus, Rosellinia necatrix megabirnavirus 2 (RnMBV2) (A. Sasaki, personal communication). Transfection with purified RnPV1 particles showed that RnPV1 alone conferred neither hypovirulence nor any symptoms (22).…”
mentioning
confidence: 99%
“…Due to the lack of effective control measures, virocontrol (biological control) of the disease using mycoviruses that attenuate the fungal virulence is an attractive option (13,29,30). To this end, an extensive search of a large number of field isolates was conducted allowing the detection of diverse dsRNA viruses such as a bipartite dsRNA virus, Rosellinia necatrix megabirnavirus 1 (RnMBV1), a quadrivirus, Rosellinia necatrix quadrivirus 1 (RnQV1), the reovirus mycoreovirus 3 (MyRV3), and the Rosellinia necatrix partitiviruses 1 and 2 (RnPV1 and RnPV2) (13,17,(31)(32)(33)(34)(35). Some of these viruses were shown to be able to confer hypovirulence under laboratory conditions.…”
mentioning
confidence: 99%